Fighting against drought in Dobrogea by protective forest belts - Aurel Lup; Liliana Miron (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Dobrogea province is composed by Constanta and Tulcea counties, situated in the South-eastern part of Romania, and it is known as one of the driest parts of Romania. The yearly amount of precipitations is no more than 400-450 mm. The yearly average temperature is around 10.5oC; the soils are of good quality but the main factor limiting the crops is, in this case, the lack of the water. During 1949 and 1955, studies were carried out concerning the damages produced by drought and the influence of the forest plantations for protective purposes on crops. Consequently, there have been planted protective forests on a few thousand hectares in the southern part of Constanta county but which were insufficient in order to protect all the agricultural lands. Because of the uncertainty surrounding the rehabilitation of the irrigation systems in the near future in Dobrogea, several projects were made in order to set up protective forest plantations. These projects include 70 localities and there have already been planted protective forests in some of them. The width of these forests is 10 m, the planting scheme is 2 x 1 m, and the distance between them is variable, by the case. The locust tree is the used species
Keywords: 330; drought; damage; forest belt